A comparative study of static pulmonary function tests in Indian pregnant and non-pregnant women - Fadia, Ameet; Dhadse, Manish (International Journal of Research in Medical Sciences, 2016)
Background: Pregnancy represents one of the best examples of selective adaptation in terms of respiratory physiology. Objective of the study is to evaluate the changes in static pulmonary function tests (PFTs) in third trimesters of pregnancy (study group) and compare with non-pregnant women (control group). Methods: 65 subjects (study group 35 subjects and control group 30 subjects) from a tertiary care hospital of Mumbai were included in the study. Pulmonary function tests (PFTs) was done by computerized spirometry. Results: Statistical analysis was carried out and paired t-test was applied. Significant increase in mean inspiratory capacity and significant decrease in mean expiratory reserve volume were observed in the third trimester of normal pregnant women as compared to normal non-pregnant women. Conclusions: The present study highlights observation that there is no respiratory impairment due to pregnancy, as adaptive changes in respiratory system compensate for the altered structure and function of the maternal body and very well suffice for the increased needs of pregnancy.